PENATALAKSANAAN COOL PACK TERHADAP PENURUNAN TINGKAT NYERI SAAT PEMASANGAN INFUS PADA PASIEN ANAK TIFOID DIRUANG IGD - Renny Triwijayanti (IKesT Muhammadiyah Palembang, 2024)
Background: Typhoid fever is an acute infectious disease that attacks the digestive tract and is caused by Salmonella typhi bacteria with symptoms of increased body temperature. Hyperthermia will also increase the risk of fluid volume deficiency (dehydration). One action to overcome this is by inserting fluids through an IV. However, nurses must respect the child's concerns about pain reactions. Therefore, efforts are needed to reduce pain due to the procedure provided by installing a Cool Pack. The Cool Pack, which is previously placed on the hand where the infusion will be installed, is able to reduce the level of pain because this therapy produces an analgesic effect by slowing down the speed at which pain impulses reach the brain. Objective: Management of Cool Pack in two patients to reduce the level of pain during infusion in pediatric typhoid patients in the Emergency Room of Muhammadiyah Hospital Palembang. Method: This method uses observation, interviews and assessment instruments with primary and secondary data collection techniques for 2 days from 06 May 2023 to 07 May 2023. Results: After administering the Cool Pack, the results obtained were that there was an effect from giving Cool Pack before installing the infusion. The first patient had a pain scale result: 5, and the second patient had a pain scale result: 5. Conclusion: Cool Pack management was good for reducing the level of pain during infusion in both patients. Suggestion: Cool Pack management is expected to be one of the treatment interventions to reduce the level of pain during infusion and not only in pediatric typhoid patients, but also in other pediatric patients who will undergo infusion. Keywords: Typhoid, Hyperthermia, Dehydration, Cool Pack, Infusion, Pain